Combined proximal balloon occlusion and distal aspiration: a new approach to prevent distal embolization during neurothrombectomy. (7th April 2016) - Stampfl, Sibylle; Pfaff, Johannes; Herweh, Christian; Pham, Mirko; Schieber, Simon; Ringleb, Peter A; Bendszus, Martin; Möhlenbruch, Markus A
Abstract : Background and purpose: Embolization of thrombus fragments in a new vascular territory is a potential adverse event in neurothrombectomy. This study was performed to evaluate the safety and feasibility of a novel approach combining proximal balloon occlusion and distal aspiration to prevent distal thrombembolic complications. Methods: Patients with ischemic stroke meeting the following inclusion criteria were eligible: occlusion in the anterior circulation, neurothrombectomy using a balloon catheter for proximal flow arrest, and an intermediate catheter for distal aspiration. Pre- and post-interventional Thrombolysis In Cerebral Infarction (TICI) scores were assessed. Clinical presentation at admission and discharge and after 3 months was also evaluated and complications (particularly new thrombembolic events) were recorded. Results: We retrospectively identified 31 patients from our prospectively collected stroke database who met the inclusion criteria. In all patients the initial TICI was 0. A TICI score of ≥2b was achieved in 96.8%. No new thrombembolic complications occurred. The median NIH Stroke Scale score was 19 at admission and 4.5 at discharge. After 3 months, 51.6% of the patients had a favorable clinical outcome (modified Rankin Scale score 0–2) and 19.3% had died. Conclusions: A combination of proximal internal carotid artery occlusion using a balloon catheter and distal aspiration through an intermediate catheter represents a safe and efficient adjunct to mechanical thrombectomy with stent retrievers. In our patient cohort, no new thrombembolic complications were detected.